Observing EFL teachers’ use of formulaic language in class - Ton Nu Linh Thoai (Universitas Katolik Indonesia Atma Jaya, 2020)
Mastering formulaic language is said to be crucially important in second language (L2) learning as it showcases the L2 user’s different levels of competency: linguistic, psycholinguistic, and communicative. Frequent use of these formulaic sequences also makes an L2 speaker sound more native–like. In a language teaching and learning context where English is a foreign language (EFL), the language teacher is the one major resource of spoken language exposure. Therefore, the quality of teacher’s instructions in an EFL classroom clearly has effects on the learner’s language learning process. Mercer (2001) puts it, “[a]ll […] aspects of teacher’s responsibility are reflected in their use of language as the principal tool of their responsibilities” (p. 243). A great deal of research has been devoted to L2 learners and the acquisition of formulaic language, and classroom interaction, but very little attention has been paid to teachers’ use of formulaic sequences in their classrooms. This paper presents a descriptive study with analytical discussion of extracts from four video–recorded lessons conducted by school teachers in different South–east Asian countries. This small-scale study attempts to explore to what extent non–native EFL teachers are familiar with and use formulaic language during class time.